ANALISIS DETERMINAN KINERJA KARYAWAN PT. PELINDO (PERSERO) TBK. IV. CABANG MAKASSAR - Ashar, Muh.; Hikma, Nurul (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
This study aims to determine (1) the deciding factor (determinant) the performance of employees of PT. Pelindo (Persero) Tbk. IV Makassar branch either simultaneously or partially to the work environment, compensation, training and career development (2) the dominant factors affect the performance of employees of PT. Pelindo (Persero) Tbk. IV Branch Makassar.This study uses survei.Responden association through this study are employees PT.Pelindo (Persero) Makassar Tbk.IV.Cabang of the 100 people who were taken through methods Slovin. Data collected through observation, interviews